(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The purpose of our study was to identify reasons for high dropout of students enrolled in the first year of the computer science study program to make it possible to determine students, who are potentially in risk. Several factors that could affect attrition, as it was originally assumed, were studied: high school grades (admission score), compensative course in high school mathematics, intermediate grades for core courses, prior knowledge of programming. However, the results of our study indicate that none of the studied factors is determinant to identify those students, who are going to abandon their studies, with great precision. The majority of the studied students drop out in the 1st semester of the 1st year, and the dropout consists mostly of those, who do not really begin studies. Therefore, one of the main conclusions is such that the planned activities of informing about the contents of the program should be carried out, and the perspective students should be offered a possibility to evaluate their potential to study computer science before choosing a study program.